Prevention of administrative violations of the right to information - Чуприна, Олена Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The analysis of national legislation and scientific sources to prevent administrative violations, the main determinants of violations of the right to information, and suggested the main ways to prevent them.